STRATEGI PENGEMBANGAN AGROINDUSTRI GULA AREN DI DESA TONDEI 1 - Novita ., Wongkar; Joachim N. K. Dumais; Theodora M. Katiandagho (AGRI-SOSIOEKONOMI, 2017)
The purpose of this research is to identify the right development strategy in Tondei Village 1, Sub-district of West Motoling, South Minahasa Regency. The research was conducted in September until November 2017, using primary and secondary data with 10 respondents. Data primary collection through interviews using questionnaires. Secondary data collected from the office of Tondei 1 Village. Research data in the analysis using SWOT analysis. The result of the research shows that the result of internal strategic factor analysis shows that the total score of internal analysis result is 3.16 indicating that it is in a "moderate" position in harnessing the strength to face the weakness faced in the development of sugar palm agroindustry in Tondei Village 1. Result of external strategic factor analysis through opportunity and threatened to get a total score of its external analysis is 3.26 which indicates that the development of sugar palm agro-industry is in a strong external position in exploiting the opportunity to overcome the threats faced.*jnkd*